KEADILAN SOSIAL DALAM PERLINDUNGAN KEPENTINGAN NASIONAL PADA PENANAMAN MODAL ASING BIDANG SUMBER DAYA ALAM - Widhayani Dian Pawestri (Universitas Airlangga, 2015)
Prioritizing the social justice to protect national interests based on constitution becomes one of the problems in our economic development, especially in foreign direct investment of natural resources. UUD NRI 1945 as the economic constitution is the fundamental basis to make a foreign direct investment policy. Similar to embodying justice, State has to prioritize social justice and stand on the national interests so that state can achieve its purpose through foreign direct investement.